2019
DOI: 10.1039/c9dt01753d
|View full text |Cite
|
Sign up to set email alerts
|

Actinyl-cation interactions: experimental and theoretical assessment of [Np(vi)O2Cl4]2− and [U(vi)O2Cl4]2− systems

Abstract: Interactions between the Li+ cation and the neptunyl(vi) oxo observed in both solid state and aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…The structure of 3 is further unusual in that the unit cell contains two (Cp′ 3 Y II ) 1– anions with the charge balanced by a [(THF)­Na 2 (18c6) 2 ] 2+ dication that has two different types of Na 1+ coordination environments. The [Na 2 (18c6) 2 ] 2+ dication has previously been observed in several structures, but never with a single additional THF molecule. Hence, this structure adds another example to the many variations of countercations composed of alkali metal cations and 18c6 .…”
Section: Resultsmentioning
confidence: 85%
“…The structure of 3 is further unusual in that the unit cell contains two (Cp′ 3 Y II ) 1– anions with the charge balanced by a [(THF)­Na 2 (18c6) 2 ] 2+ dication that has two different types of Na 1+ coordination environments. The [Na 2 (18c6) 2 ] 2+ dication has previously been observed in several structures, but never with a single additional THF molecule. Hence, this structure adds another example to the many variations of countercations composed of alkali metal cations and 18c6 .…”
Section: Resultsmentioning
confidence: 85%
“…22 DFT was also used to observe the emergence of an additional ν 1 band in a Np(VI)O 2 2+ /Li + system due to the occurrence of actinyl-cation interactions in solution. 16 These studies highlight the value of DFT to interpret the complex vibrational bands that arise in actinyl systems and can be applied to further understand AAIs within these systems.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7][8][9][10][11][12] In addition, this particular bonding motif imparts significant influence on the chemistry in aqueous and solid-state systems, resulting in overall changes in its redox properties, 13,14 disproportionation reactions, 15 and complex vibrational and electronic spectroscopy. 13,14,16,17 Therefore, it is crucial to understand both the bonding within the actinyl cation and the additional interactions within the solid and solution phases to develop an in-depth, systems-level approach to the chemistry of the high-valent early actinides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies showed that often the frequencies observed are coupled modes of multiple vibrations and not normal modes obfuscating the correlation of the observed frequencies with other metrical parameters, as is typically done with complexes of uranium(VI). 34,35 ■ CONCLUSION The syntheses of two new neptunium complexes from strongly alkaline solutions of potassium and rubidium hydroxide are reported here and their structures determined from singlecrystal X-ray diffraction. Raman spectra of these complexes have been recorded and reported.…”
Section: ■ Raman Spectroscopymentioning
confidence: 97%